Evaluation of Extraction Buffers for Protein Identification in Fish Paste with Chicken Blood Plasma (CBP) Spikes: A Preliminary Mass Spectrometry Study - Azmi, Nurhazirah; Abidin, Siti Aimi Sarah Zainal; Zakaria, Nurkhurul Ain; Shukor, Mohd Syarafuddin Abdul; Karsani, Saiful Anuar; Fatt, Low Kim; Yuswan, Mohd Hafis (Universitas Gadjah Mada, 2025)
Blood plasma is commonly used as a protease inhibitor in surimi production to improve product quality and stability during processing. However, its use in food is prohibited in Islam and classified as najs al-mutawasitah, necessitating the detection of blood plasma adulteration to uphold halal standards and food safety. This study compared the effectiveness of different extraction buffers—ultrapure water, 0.05 M Tris-HCl, 0.05 M Tris-Urea, and ultrapure water followed by acetone precipitation—on protein and peptide yield from chicken blood plasma (CBP) using liquid chromatography–quadrupole linear ion trap mass spectrometry (LC-QTRAP-MS). Ultrapure water and acetone precipitation yielded the highest protein content, prompting further proteome profiling of CBP, fish paste, and surimi spiked with CBP (0.5, 1, and 1.5%) via liquid chromatography–quadrupole time-of-flight mass spectrometry (LC–QTOF-MS). Apolipoprotein AI (Apo AI) and fibrinogens emerged as key proteins in CBP. Apo AI was detected in all spiked surimi samples, demonstrating its potential as a marker for blood plasma contamination. The proposed method enhances extraction and detection protocols, using mass spectrometry to provide a reliable tool for addressing halal compliance and mitigating food safety risks associated with blood-derived adulterants in surimi products.